Evaluation of starches digestibility and glycemic index of commonly consumed staple foods from selected varieties of cassava (Manihot sp.) and yam (Dioscorea sp.) - Eyinla, T.A. (University of Ibadan, 2019)
Consumption of high Glycemic Index (GI) foods is a risk factor for increasing prevalence of metabolic related non-communicable diseases. Cassava and yam are among common staples known to have high GI and are usually avoided by diabetics because they can rapidly raise blood glucose. Currently, it is still unclear if common varieties (and their corresponding products) have different starch digestibility and GI. This study was therefore designed to evaluate starch digestibility and GI of common foods from selected varieties of cassava and yam. The study was laboratory-based and exploratory in design comprising of three stages. At preliminary stage, five common varieties of both cassava (TMS30555, TME8002, TME419, TMS30752 and TMS011371) and yam (TDr02665, Meccakusa, Oju-iyawo, Amula and Alumaco) were selected. Four products were then prepared from each variety of cassava (Eba, Fufu, Gari and Lafun) and yam (Boiled, fried, pounded yam and Amala). In stage one, Digestible Starch (DS) and Resistant Starch (RS) were determined using a standard enzymatic assay. In stage two, four products (Eba, Fufu, pounded yam and Amala) were processed from three most popular varieties of cassava (TME419, TMS30752 and TMS011371) and yam (Oju-iyawo, Amula and Alumaco). Analysis of Rapidly Digestible Starch (RDS), Slowly Digestible Starch (SDS) and estimated GI (eGI) was carried out in the second stage using standard in-vitro methods. In stage three, GI of products consumed by apparently healthy adults (n=33) was determined using standard WHO methodology. Data were analysed using descriptive statistics and correlation with significance set at α0.05. The TME 419 variety had the highest DS in all products (20.1–45.3g/100g), while TMS 011371 had the lowest RS (0.4–1.9g/100g). The RS content of all varieties were not significantly different per product. Among the varieties, Fufu had the highest RS (1.1- 2.1g/100g). Amula had the highest DS in Amala (19.1g/100g) and pounded yam (20.4g/100g) while Alumaco had the highest RS in all products (2.9 – 3.3g/100g). There was an increase in RS of Alumaco after processing into all the selected products. In stage two: TMS30572 yielded the highest RDS in both Eba (1.4g/100g) and Fufu (1.2g/100g). The eGI of TMS30572 was the highest in Eba (67) and Fufu (57). In yam, Alumaco had the lowest RDS in Amala (0.6g) and pounded yam (0.3g) while eGI was the lowest in Alumaco made into Amala (53) and pounded yam (48). Assessment of cassava varieties (TME419, TMS30752, and TMS011371) resulted in GI of Eba (88, 99, and 89), and Fufu (86, 91 and 92) respectively. In yam varieties-Oju-iyawo, Amula and Alumaco, GI results were Amala (86, 89, 83) and pounded yam (92, 97, 104). GI correlated negatively with RS in Fufu (r=-0.981) but positively in Amala (r=0.957) while eGI correlated positively with GI in Eba (r=0.975), Fufu (r=0.845) and Amala (r=0.242). Cassava varieties made into Fufu and all products from yam variety-Alumaco showed favorable properties applicable for controlling rapid post-prandial rise in blood glucose. Exploring more processing methods and crop diversity is hereby recommended.